Foreign Direct Investment and Gross Domestic Product in Kazakhstan - Katenova, Maya (International Journal of Economics, Business and Management Studies, 2019)
The study explores a relationship between foreign direct investment and gross domestic product in Kazakhstan. It was found that, in general, Kazakhstan remains the leader in the sphere of investment attracting among the Central Asian countries. The risks of investing in other countries of Central Asia seriously exceed the risks of investing in Kazakhstan. The capital and investment, along with human resources, is an important development center. Foreign direct investment played an important role in the economic growth of developed countries. Almost every developed country has assisted foreign financial institutions in addition to its own small savings in the early stages of its development. Kazakhstan is known as a developing country in the center of Eurasia, which attracted over 151 billion of USA dollars since its independence. The aim of the study is to find out the relationship between foreign direct investments and Gross Domestic Product. The study proved the fact that foreign direct investment does significantly positively affect Gross Domestic Product in Kazakhstan. Thus, we can make a practical conclusion that these results can be helpful as a base for the new researches as well as for the practical implementation and potential government’ use in Kazakhstan. The further research may employ such variables as exchange rate, inflation rate. Some new methods can be employed such as Ordinary Least Squares. Practically, policy makers should take into consideration the fact that foreign direct investment positively and significantly affects Gross Domestic Product.